2004
DOI: 10.1074/jbc.m408062200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Sarcoplasmic Reticulum Ca2+-ATPase from ATP and ATP Analogs Studied by Infrared Spectroscopy

Abstract: Phosphorylation of the sarcoplasmic reticulum Ca 2؉ -ATPase (SERCA1a) was studied with time-resolved Fourier transform infrared spectroscopy. ATP and ATP analogs (ITP, 2 -and 3 -dATP) were used to study the effect of the adenine ring and the ribose hydroxyl groups on ATPase phosphorylation. All modifications of ATP altered conformational changes and phosphorylation kinetics. The differences compared with ATP increased in the following order: 3 -dATP > ITP > 2 -dATP. Enzyme phosphorylation with ITP results in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…AURKA has been shown to directly phosphorylate p53 at Ser-215 and Ser-315 which abrogates p53 DNA binding and transactivation of target genes (Liu et al, 2004), and promotes MDM2-mediated destabilization and inhibition of p53 (Katayama et al, 2004). There is additional evidence to suggest that AURKA can also inhibit p53 via the AKT/MDM2 axis in gastric cancer cells, however this remains to be shown in neuroblastoma (Dar et al, 2008).…”
Section: P53mentioning
confidence: 99%
See 1 more Smart Citation
“…AURKA has been shown to directly phosphorylate p53 at Ser-215 and Ser-315 which abrogates p53 DNA binding and transactivation of target genes (Liu et al, 2004), and promotes MDM2-mediated destabilization and inhibition of p53 (Katayama et al, 2004). There is additional evidence to suggest that AURKA can also inhibit p53 via the AKT/MDM2 axis in gastric cancer cells, however this remains to be shown in neuroblastoma (Dar et al, 2008).…”
Section: P53mentioning
confidence: 99%
“…In neuroblastoma AURKA has been found to be expressed at high levels in MYCN amplified tumors and required for the growth of MYCN amplified cells (Berwanger et al, 2002; Otto et al, 2009). Studies have shown that it suppresses p53 transcriptional activity as well as promoting increased MDM2-mediated p53 degradation (Katayama et al, 2004; Liu et al, 2004). Additionally, via direct interaction but in a kinase independent manner, AURKA has been reported to stabilize MYCN by preventing its ubiquitin mediated degradation (Maris, 2009; Otto et al, 2009).…”
Section: P53mentioning
confidence: 99%
“…Interestingly, Trumble et al [1981] found that the NTPase activity and Ca 2+ removal by the sarcolemmal (SL) ATPase transporter contrasted with that of SERCA2 by decreasing ~40% when dATP replaced ATP. Liu and Barth [2004] examined structural changes of SERCA1a (fast skeletal) with dATP versus ATP utilizing IR spectroscopy, and found the phosphorylation spectra of both to be very similar. This indicates that the 2’-OH has very little effect on the conformational change of SERCA, at least in skeletal muscle, upon phosphorylation.…”
mentioning
confidence: 99%
“…Using the COBSI index, one can estimate the net change of a secondary structure in a partial reaction. In reality, there is significant overlap of the absorption spectra for the two states (20,114). The values for 100% secondary structure transition of an ordered to an unordered structure are in the range of 0.2-0.6, which corresponds to redistribution of 20 to 60% of integrated absorbance upon transition (20).…”
Section: Estimation Of Secondary Structural Changes Upon Ligand Bindimentioning
confidence: 97%